Kerala’s cashew workers - Manja Bomhoff (IIAS Newsletter, 2007)
Review of the Book: Lindberg, Anna. 2005. Modernization and Effeminization in India: Kerala Cashew Workers since 1930. Copenhagen: NIAS Press. 200 pages, ISBN 87 91114 21 7